2008
DOI: 10.1021/ja0760877
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Microbial Arginine Deiminases by l-Canavanine

Abstract: Arginine deiminase (ADI) catalyzes the hydrolytic conversion of L-arginine to ammonia and L-citrulline as part of the energy-producing L-arginine degradation pathway. The chemical mechanism for ADI catalysis involves initial formation and subsequent hydrolysis of a Cys-alkylthiouronium ion intermediate. The structure of the Pseudomonas aeruginosa ADI-(L-arginine) complex guided the design of arginine analogs that might react with the ADIs to form inactive covalent adducts during catalytic turnover. One such ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 48 publications
2
32
0
1
Order By: Relevance
“…In contrast, our preliminary data suggest that the effective canavanine dose increased considerably when the preparation of recombinant Mycoplasma hominis arginine deiminase was co-administered with canavanine, making this combination less feasible (data not shown). This may be explained by the fact that arginine deiminase can be efficiently inhibited by canavanine [46,49]. As the catalytic properties of pegylated recombinant human arginase do not differ significantly from those of the native human enzyme [9], our data suggest that canavanine is a suitable agent for combined treatment with arginase preparations and warrant further studies on its clinical potential.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, our preliminary data suggest that the effective canavanine dose increased considerably when the preparation of recombinant Mycoplasma hominis arginine deiminase was co-administered with canavanine, making this combination less feasible (data not shown). This may be explained by the fact that arginine deiminase can be efficiently inhibited by canavanine [46,49]. As the catalytic properties of pegylated recombinant human arginase do not differ significantly from those of the native human enzyme [9], our data suggest that canavanine is a suitable agent for combined treatment with arginase preparations and warrant further studies on its clinical potential.…”
Section: Discussionmentioning
confidence: 73%
“…However, in the case of a combination of arginine starvation with canavanine treatment, it should be taken into consideration that canavanine, as an arginine analogue, is also a substrate of these enzymes [44,45]. When a recombinant enzyme and the drug are administered simultaneously, this could lead to partial detoxification of canavanine, or, alternatively, canavanine, as the competitive arginine analogue, can inhibit activity of the enzymes that are mentioned [46,47]. However, we showed that at a 0.1 mmol/l concentration canavanine did not inhibit bovine liver arginase activity in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographically, MaAD was observed as a dimer [8] whereas the PaAD (shown in Fig. 3B) [29] and BcAD [30] were characterized as dimers of dimer. The GlAD C-terminal domain does not impede formation of the subunit-subunit interface of the dimer.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the reported crystal structures of MaAD, PaAD and BcAD [7,8,30] provided us with structural templates for the construction of a three-dimensional model of the GlAD N-terminal (“catalytic”) domain (residues 1–434). The GlAD model, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation